Advanced Research of Abdominal Aortic Aneurysms on Metabolism - Hou, Yangfeng; Guo, Wenjun; Fan, Tianfei; Li, Bolun; Ge, Weipeng; Gao, Ran; Wang, Jing (Frontiers in Cardiovascular Medicine, 2021)
Abdominal aortic aneurysm (AAA) is a cardiovascular disease with a high risk of death, seriously threatening the life and health of people. The specific pathogenesis of AAA is still not fully understood. In recent years, researchers have found that amino acid, lipid, and carbohydrate metabolism disorders play important roles in the occurrence and development of AAA. This review is aimed to summarize the latest research progress of the relationship between AAA progression and body metabolism. The body metabolism is closely related to the occurrence and development of AAA. It is necessary to further investigate the pathogenesis of AAA from the perspective of metabolism to provide theoretical basis for AAA diagnosis and drug development.